Nicotinamide phopshoribosyltranferase (NAMPT_ 7q22.3). - Koumaki, V; Dalamaga, M (Atlas Genet Cytogenet Oncol Haematol., 2012)
Because of its pivotal role in the recycling pathway allowing NAD generation from nicotinamide, NAMPT occupies a central position in controlling the activity of several NAD-dependent enzymes. NAD, a universal energy-and signal-carrying molecule and its phosphorylated form, NADP, are required in several intracellular processes such as redox reactions, DNA repair, G-protein coupled receptor signaling, intra-cellular calcium-mobilizing molecules, transcriptional regulation, mono-adenosine diphosphate (ADP)-ribosylation in immune response, and activity of poly-ADP ribosyltransferases and deacetylases (sirtuins) with roles in regulating cell survival and cytokine responses. Under the influence of NAMPT, adequate levels of NAD control SIRT-6 (sirtuin) activity, which in turn positively regulates TNF-α mRNA translation favoring cell survival. NAMPT activity enhances cellular proliferation, tips the balance toward cellular survival following a genotoxic insult and controls the circadian clock machinery of some key transcriptions factors.